Do Effects of Client Preference on Accounting Professionals' Information Search and Subsequent Judgments Persist with High Practice Risk? - Kadous, Kathryn; Magro, Anne M.; Spilker, Brian C. (The Accounting Review, 2008)
Prior research indicates that audit and tax professionals' judgments are influenced by their client's preferences, both directly and indirectly (via information search). In an experiment with tax professionals as participants, we examine whether high practice risk (i.e., exposure to monetary and nonmonetary costs of making inappropriate recommendations) mitigates these effects. We find that, when facing a client with low practice risk, professionals' search is biased in a manner that leads judgments to be consistent with client preference; however, search is less biased when facing a client with high practice risk, and resulting judgments are less consistent with client preference. We also find that, after controlling for the impact of information search, professionals tend to adjust their recommendations away from the client-preferred position, regardless of practice risk. This study sheds light on the direct and indirect paths by which client preference and practice risk affect professionals' judgments.